Problems of Intensification and Economic Growth - Daskovsky, Vadim B.; Kiselyov, Vladimir B. (Problems of economic transition, 2018)
Russia's long-term lack of viability in the world economy could lead to it becoming a third-world country. When it comes to economic regulation, the only principle the Russian government has adopted from liberal economics is that of governmental noninterference. The "Growth Strategy" program developed by the Stolypin Club, based on real demands and constructive principles, outlines how the Russian economy can recover from the current crisis.